RESILIENCE AND WELL-BEING AMONG ORPHANS IN MALAYSIA: A MULTIDIMENSIONAL PERSPECTIVE - Usman Jaffer; Che Mohd Nasril Che Mohd Nassir; Mohamed Ayaaz Ahmed; Rahmah Ahmad H. Osman; Muhammad Hafiz Khuzaifiz Ilias; Muhammad A’limu Al-Ssalam Mohd Yusoff; Izzati Fathini Khuzairi; Aliana Aishah Jaafar; Nur Athilah Iwani Abdul Manan; Siti Aisyah Najwa Zakaria, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study investigates the well-being of orphans in Malaysia, focusing on their social, religious, and psychological dimensions. Drawing upon existing literature, the research explores the unique challenges faced by orphans, emphasising the need for resilience in the face of adversity. The study employs quantitative methods, using structured questionnaires to assess the well-being of eight female orphans aged 7 to 9 years and a 24-year-old caregiver at PJHKS, an orphanage in Kuantan, Pahang. The questionnaires cover aspects of demographic, social, religious, and psychological well-being. Statistical analysis reveals robust social well-being among the orphans, with an average score of 73%, and a strong adherence to religious practices. However, their psychological well-being reports a moderate average of 64%, indicating emotional and mental challenges. The study finds that the orphans exhibit positive social skills and attitudes, and their religious well-being is significantly shaped by the caregivers' dedication to Islamic teachings. However, psychological challenges persist, necessitating further support and intervention. The research emphasises the crucial role of comprehensive care in enhancing the overall well-being of orphans and calls for more targeted efforts to address their diverse needs. The findings contribute to a deeper understanding of orphan well-being in Malaysia and offer insights for policy and practice in orphan care.